The Role of Legal Rules in Protecting the Atmospheric Environment from Pollution by the Oil Industries - Fadhil Gatea, Researcher. Atyaf; Jabbar Kraidi , Prof. Dr. Ali (Basra studies journal, 2024)
The oil industries are an integral part of the national economies of many countries; however, they pose numerous environmental challenges, particularly concerning air pollution. The atmospheric environment is a crucial element for life on Earth, and pollution from oil industries can have severe effects, threatening both the environment and human health. This has led to the establishment of agreements aimed at protecting the atmospheric environment from pollution originating from various sources. The atmospheric environment is one of the most important natural resources relied upon by humans and life on Earth. To address emerging challenges and maintain a safe, pollution-free environment, several international agreements have been established to protect the atmospheric environment. Therefore, it is necessary to review these agreements, analyze their roles, and evaluate their effectiveness in combating pollution caused by the oil industries. At the international level, a number of agreements have been made to protect the atmospheric environment from pollution from different sources. However, within the scope of our study, we will focus on the most significant of these agreements and their effectiveness in protecting the atmospheric environment from pollution caused by the oil industries.